Zinc Glycine supplementation improves bone quality in meat geese by modulating gut microbiota, SCFA's, and gut barrier function through Wnt10b/NF-κB axis - Zeshan Zulfiqar; Muhammad Arslan Asif; Mengqi Liu; Shuhang Zhang; Hamid reza Rafieian Naeini; Yalei Cui; Boshuai Liu; Yinghua Shi (Poultry Science)
Bone disorders are characterized by leg abnormalities and alterations in gut microbiota, which are linked with destruction of bone structure and increased risk of fractures. Zinc (Zn) plays a crucial role in normal bone homeostasis and has been proven to be highly effective against leg problems. The effects of different Zn sources on bone quality were evaluated in this study. A total of 300 one-d-old Wanpu mixed-sexed geese fed 2 basal diets added with best suited levels of 80 mg/kg inorganic zinc (ZnSO4), and 80 mg/kg Organic zinc (Zn-Glycine) for 60 d. Tibia bone mineral density (BMD), ash percentage, and tibia length increased with dietary Zn source (P < 0.05). Micro-computed tomography analysis revealed that Zn-Glycine improved bone mass, potentially due to an increased abundance of Firmicutes and higher SCFA production in the cecum. Dietary Zn Glycine addition reduced intestinal permeability, upregulated the protein expression of tight junction protein (Zonula Occludens-1, Claudin-1), downregulated diamine oxidase (DAO) levels, and increased the abundance of Lactobacillus and Bifidobacterium, which was accompanied by a reduction in inflammatory cytokines levels in the serum, tibia, and cecum. In terms of bone turnover, Zn-Glycine increased alkaline phosphatase (ALP) and other bone markers (Runt-related transcription factor 2- Runx2, Osteoprotegerin- OPG, Osteocalcin- OCN, Suppressor of mother against decapentaplegic- SMAD) expression, resulting in a decrease in osteoclast number and a reduction in serum bone resorption biomarkers, including serum tartrate-resistant acid phosphatase activity and tibia nuclear factor of activated T-cells (NFATC1) and tumor necrosis factor receptor associated factor 6 (TRAF-6) (P < 0.05). Zn-Glycine also enhanced antioxidant capacity by increasing catalase (CAT) and glutathione peroxidase (GSH-PX), resulting in reduced reactive oxygen species (ROS) and malondialdehyde (MDA) production (P < 0.05). Zn-Glycine at 80mg/kg in the diet actively reduced (P < 0.05) the expression of cell-death-associated proteins (Beclin-1, Caspase-3). Additionally, Zn-Glycine improved intestinal morphology (villus height, villus-to-crypt ratio), supporting efficient nutrient absorption. Immunofluorescence analysis of tibia showed higher expression of wingless type-10b (Wnt-10b) and reduced expression of nuclear factor-kappa B (NF-κB) in Zn-Glycine group compared to ZnSO4 group. These findings underscore the significance of the gut-bone axis and provide new insights into the effect of Zn-Glycine on bone health in meat geese through a key signaling pathway.